EFEKTIVITAS PENERAPAN MEDIA PEMBELAJARAN KOMIK IPA TERHADAP HASIL PEMBELAJARAN IPA PESERTA DIDIK KELAS IV SEKOLAH DASAR - Wira Zain Amrullah, Lalu; Irawan Zain, Moh; Ramadhani, Miatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The goal of this research is to ascertain how well science comic media application affects fourth-grade elementary school students' science learning results. This kind of study uses a nonequivalent control group design and is quantitative in nature, with a quasi-experimental design. Students in grade IV at SDN 37 Cakranegara served as the study's subjects. Saturated sampling, a non-probability sampling approach, was the method employed. The independent sample t test was employed as the hypothesis test, and the normality and homogeneity tests were prerequisites that had to be satisfied. With an effect size value of 1.005, the independent sample t-test findings showed that Ha is accepted and H0 is rejected with a t count> t table value of 3.179> 2.024 and a sig. (2-tailed) value <0.05, specifically 0.003 <0.05. The use of science comic media to the science learning outcomes of fourth-grade students at SDN 37 Cakranegara has been found to be successful, according to the study's findings.